Enhancing capacity to comply with sustainability standards in the milk value chain in East Africa: Challenges, prospects, and policy implications - Kilima, F.T.M.; Msalya, G.M.; Omore, Amos O. (MDPI, 2024)
This paper addresses the need to contextualize sustainability standards and supply chain management in dairy value chains in East Africa, where milk perishability and limited cold storage significantly impact the industry. The study highlights the importance of localizing these standards, given the greater dependence on local supply chains following the COVID-19 pandemic. Drawing on milk standards literature and various interventions aimed at promoting systemic change, this review analyses the capacity of marginalized stakeholders in East Africa’s dairy value chains to meet sustainability standards, focusing particularly on the social dimensions of these standards. The findings indicate that compliance with sustainability and safety standards is predominantly restricted to formal dairy networks, which process less than 20 percent of milk produced in the region. Most milk sales occur through informal or unorganized markets, which face significant barriers to meeting international sustainability benchmarks. The review advocates for the alignment of international sustainability standards with the unique conditions of the informal markets dominating East Africa’s dairy sector. It suggests enhancing stakeholder capabilities and addressing regulatory barriers as necessary steps for improving compliance with these standards. The co-operative model is highlighted as a promising approach to integrating farmers and marginalized value chain actors into the formal sector, thereby facilitating incremental adoption of sustainability standards. The paper identifies strategic entry points for organizing and upgrading the supply chain, including capacity building, certification, and catalyzing farmer groups to compliance and productivity.